Influence of the human activity on wide-band characteristics of the 60 GHz indoor radio channel. - Collonge, S.
This paper presents propagation measurements in the presence of human activity for a 60 GHz channel. Series of 40-min-long measurements of the channel impulse response have been recorded with a sampling period of 1.6 ms, for a total duration of about 20 h. During measurements, the human activity (between zero and 15 persons) was observed with a video camera. The obstruction phenomenon due to the human bodies is characterized in duration and amplitude from the propagation characteristics (attenuation, coherence bandwidth) by means of an appropriate method. The results highlight and quantify the problems due to the human activity for high data rate communication systems. When the direct path is shadowed by a person, the attenuation generally increases by more than 20 dB, for a median duration of about 100 ms for an activity of one to five persons and 300 ms for 11-15 persons. Globally, the channel is "unavailable" for about 1% or 2% of the time in the presence of one to five persons. This channel characterization makes it possible to modelize the temporal variations of the 60 GHz channels. The results also give orientations for the design of high data rate communications systems and networks architectures at 60 GHz.
Keywords: 60 GHz; Attenuation; Channel impulse response; Channel sounding; Coherence bandwidth; Data rate communications system; Human activity; Indoor radio channel; Millimeter wave; Time-varying channel; Wideband characteristic